Syndromic Testing—The Evaluation of Four Novel Multiplex Real-Time Polymerase Chain Reaction Panels - Mesut Yılmaz; Selcuk Kilic; Fatma Bayrakdar; Selin Nar Ötgün; Ayse Istanbullu Tosun; Umit Zeybek; Faruk Çelik; Gokhan Aygun; Birol Safak; Naim Mahroum (Diagnostics)
Background: If used in the right clinical context, PCRs carry great potential in rapidly diagnosing various infectious diseases. Objectives: We aimed to evaluate the clinical performance of four novel multiplex real-time PCR (qPCR) assays in the direct detection of pathogens in whole blood, cerebrospinal fluid, respiratory specimens, and stool samples. Methods: Spiked negative clinical specimens were used for the evaluation. Clinical samples for the comparative assessment of culture and molecular analyses were simultaneously examined. RINATM robotic nucleic acid isolation system and Bio-Speedy® multiplex qPCR panels (Bioeksen R&D Technologies, Turkey), and the LightCycler® 96 Instrument (Roche, USA) were used for the molecular testing. Results: No qPCR assays produced positive results for the samples spiked with the potential cross-reacting pathogens. The limit of detection (LOD) of the assays changed with the use of 10 and 100 pathogens/mL sample based on the target and sample type. The relative sensitivity and specificity of the assays were, respectively, 82% and 94% for blood, 97.1% and 99.3% for blood culture, 94% and 98% for stool, 96% and 97% for CSF, and 97% and 96% for respiratory specimens. Conclusions: The panels evaluated allow the direct molecular analysis of 10 samples from four clinical syndromes on the same run in 3 h with high clinical performance. The number and variety of samples in a single run enable healthcare providers to rapidly and efficiently diagnose and treat various infections.